Application of Atterberg Limits for Predicting Soil Compaction Characteristics - Ali M. Mouloud; Asem A. Hassan (Academic Science Journal)
Compaction of soil at engineering construction sites is essential to enhance its geotechnical properties. Laboratory Standard and Modified compaction tests have been used to determine compaction characteristics namely Optimum Moisture Content OMC and Maximum Dry Density MDD. However, these tests are relatively time consuming, require considerable efforts and large soil quantities to evaluate the suitability of soils used in different engineering works. The current study aims to correlate soil compaction characteristics and their Atterberg Limits (Liquid LL and Plastic Limit PL) for soil samples collected at 1-1.25m depth from the campus site of University of Diyala, Baqubah City. Such correlations are advantageous to predict OMC and MDD needed to control field compaction specifications. Grain size analysis, specific gravity, LL, PL, standard Proctor compaction tests were carried out according to American Society for Testing and Materials ASTM Standards. The laboratory results showed that, based on Unified Soil Classification System USCS, the soil at the site is of CL type (clayey soil of low plasticity). Compaction tests revealed that OMC and MDD values were ranged from (15.8-18.4%) and (1.65-1.73)gm/cm3, respectively. MDD and OMC were correlated with their LL and PL. It was found that MDD correlates very well with LL and PL with high R2 equals to 0.8665 and 0.9189, respectively, and OMC correlates with LL and PL with less R2 equals to 0.4781 and 0.6882, respectively. The presented models were validated using the laboratory results. Correlations established in this work are useful for the preliminary evaluation of soil compaction parameters using Atterberg Limits for future engineering constructions in the study area.